2011
DOI: 10.2147/ijn.s22953
|View full text |Cite
|
Sign up to set email alerts
|

Entrapment in phospholipid vesicles quenches photoactivity of quantum dots

Abstract: Quantum dots have emerged with great promise for biological applications as fluorescent markers for immunostaining, labels for intracellular trafficking, and photosensitizers for photodynamic therapy. However, upon entry into a cell, quantum dots are trapped and their fluorescence is quenched in endocytic vesicles such as endosomes and lysosomes. In this study, the photophysical properties of quantum dots were investigated in liposomes as an in vitro vesicle model. Entrapment of quantum dots in liposomes decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 78 publications
1
2
1
Order By: Relevance
“…Generalov et al . observed a decrease of the QD655 average luminescence decay time upon encapsulation in phospholipid vesicles 39 , but this was not the case in the present study. This confirmed that the luminescence decay behaviour of quantum dots is strongly dependent on their microenvironment.…”
Section: Resultscontrasting
confidence: 90%
See 1 more Smart Citation
“…Generalov et al . observed a decrease of the QD655 average luminescence decay time upon encapsulation in phospholipid vesicles 39 , but this was not the case in the present study. This confirmed that the luminescence decay behaviour of quantum dots is strongly dependent on their microenvironment.…”
Section: Resultscontrasting
confidence: 90%
“…30 min. A similar uptake pattern has been reported for QD610-loaded liposomes 33 as well as for QD655 (PEG)-loaded liposomes 39 . The intracellular luminescent spots could be attributed to aggregates of quantum dots formed intracellularly 19,20,75,76 .…”
Section: Resultssupporting
confidence: 85%
“…The result revealed that the control CQDs have an average diameter of 22.9 nm, whereas the dual-ligand CQDs exhibit a smaller average diameter of 12.4 nm (Figure S2). The increased diameter in the control CQDs is attributed to their CQD fusion, which increases the hydrodynamic diameter of CQDs . In contrast, the dual-ligand CQDs exhibit diameters measured in DLS (12.4 nm) that are similar to those measured by TEM (11.8 nm), indicating a more uniform size distribution with a minimized CQD fusion.…”
mentioning
confidence: 97%
“…The increased diameter in the control CQDs is attributed to their CQD fusion, which increases the hydrodynamic diameter of CQDs. 32 In contrast, the dualligand CQDs exhibit diameters measured in DLS (12.4 nm) that are similar to those measured by TEM (11.8 nm), indicating a more uniform size distribution with a minimized CQD fusion.…”
mentioning
confidence: 99%